2003
DOI: 10.1152/physiolgenomics.00148.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomal analysis of failing and nonfailing human hearts

Abstract: Heart failure is a multifactorial disease that may result from different initiating events. To contribute to an improved comprehension of normal cardiac function and the molecular events leading to heart failure, we performed large-scale gene expression analysis of failing and nonfailing human ventricle. Our aim was to define and compare expression profiles of 4 specific pathophysiological cardiac situations: 1) left ventricle (LV) from nonfailing heart; 2) LV from failing hearts affected by dilated cardiomyop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 45 publications
6
74
0
Order By: Relevance
“…and failure is thought to promote cardiac dysfunction by creating an increased load on myocytes, thus impeding sarcomere motion (20). Upregulation of ␣-tubulin detected by SAGE in this study has been previously reported in the failing human heart (44). We also identified an upregulation of the genes for actin monomer-binding proteins [protein tyrosine kinase 9-like (Ptk9l); or Twinfilin-2] and thymosin ␤10 and differential regulation of four LIM-domain proteins [Csrp1, Csrp3, Crip1, and LIM domain binding 3 (Ldb3)] (Table 2) known to interact with the filamentous actin cross-linker ␣-actinin.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…and failure is thought to promote cardiac dysfunction by creating an increased load on myocytes, thus impeding sarcomere motion (20). Upregulation of ␣-tubulin detected by SAGE in this study has been previously reported in the failing human heart (44). We also identified an upregulation of the genes for actin monomer-binding proteins [protein tyrosine kinase 9-like (Ptk9l); or Twinfilin-2] and thymosin ␤10 and differential regulation of four LIM-domain proteins [Csrp1, Csrp3, Crip1, and LIM domain binding 3 (Ldb3)] (Table 2) known to interact with the filamentous actin cross-linker ␣-actinin.…”
Section: Discussionsupporting
confidence: 71%
“…The altered expression of myosin, recognized by SAGE, involves downregulation of ␣-myosin heavy chain, previously documented in hypertrophied human heart (28,35,44), and an upregulation of myosin 1G. A new ANG II target identified by SAGE is cardiomyopathy associated 4 (Cmya4) (also known as striated muscle UNC45), which encodes a protein with a role in sarcomere organization (38).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Left ventricular cardiomyocytes are under high stress because of the high pressure in this ventricle, and more cytoprotective genes may be induced as a result. In fact, microarray analysis comparing right ventricle and left ventricle shows higher expression in the left ventricle of genes belonging to the category of cell and organism defense 24 . Dominant degeneration of the outer right ventricular wall in ARVD also supports this concept because the inner free wall is under more mechanical stress and expresses more defensive genes, such as heat shock proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray technology has been utilized to identify differentially expressed genes in terminally failing vs. non-failing human hearts as well as mouse transgenic HF models [15][16][17][18][19][20][21][22]. However, little has been done to systematically compare expression profiles between various animal models and human HF of different etiologies.…”
Section: Introductionmentioning
confidence: 99%